2020
DOI: 10.1002/asia.202000620
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Activity of Functionalized Histidine‐derived Au(I) bis‐NHC Complexes for Bioconjugation

Abstract: A series of histidine derived Au(I) bis‐NHC complexes bearing different ester, amide and carboxylic acid functionalities as well as wingtip substituents is synthesized and characterized. The stability in aqueous media, in vitro cytotoxicity in a set of cancer cell lines (MCF7, PC3 and A2780/A2780cisR) along with the cellular uptake are evaluated. Stability tests suggest hydrolysis of the ester within 8 h, which might lead to deactivation. Furthermore, the bis‐NHC system shows a sufficient stability against cys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 79 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…The detailed methodology encompassing sample preparation, PIXE analysis, concentration calculation and quality control, was as previously described. 41,42 The elemental concentrations were obtained in μg per g (of dry material) and converted to μg per 10 6 cells.…”
Section: Biological Studiesmentioning
confidence: 99%
“…The detailed methodology encompassing sample preparation, PIXE analysis, concentration calculation and quality control, was as previously described. 41,42 The elemental concentrations were obtained in μg per g (of dry material) and converted to μg per 10 6 cells.…”
Section: Biological Studiesmentioning
confidence: 99%
“…Nevertheless, these would be ideal nanomaterials for PTT. [85] For biomedical applications, further tuning of the wa-ter solubility/stability properties could be achieved using different types of hydrophilic NHCs, [43,86] including those based on amino acids, [87] whose Au(I) complexes have already the tendency to form AuNPs in aqueous solution. [88] The effect of different car-bene scaffolds would also be worth exploring.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are under way in their laboratories to investigate the mechanism of action of these complexes in more detail. 64 Sen et al reported a rationally-designed redox-active gold( i ) bis-NHC complex 32 that induces immunogenic cell death (ICD) both in vitro and in vivo . The cell viability assay showed that the complex exerted good potency against A549 (IC 50 = 0.030 ± 0.001 μM), HCT116 (IC 50 = 0.030 ± 0.002 μM), and CT26 (IC 50 = 0.405 ± 0.007 μM), which was much better than that of auranofin.…”
Section: Gold(i) Complexes As Anticancer Agentsmentioning
confidence: 99%